Pengaruh Motivasi Belajar dan Kepercayaan Diri terhadap Hasil Belajar Matematika Siswa - Azhari, Baiq Elina; Arjudin, Arjudin; Triutami, Tabita Wahyu; Hayati, Laila (FKIP Universitas Mataram, 2024)
This research aims to find out the influence of learning motivation on students mathematics learning outcomes, to find out the influence of self-confidence on students mathematics learning outcomes, and to find out the influence of learning motivation and self-confidence on students mathematics learning outcomes of grade SMP Negeri 5 Praya academic year 2023/2024. This type of research was ex post facto. The population of this research were all students of grade as many as 86 students consisting of 3 classes, namely class VIII-1, VIII-2 and VIII-3. The sample uses was sample of saturation or total sampling where the entire population was sampled in this research. Data collection techniques in this research using questionnaire and test question. The instrument of this research was in the form of a learning motivation questionnaire, self-confidence questionnaire, and a test question of students mathematics learning outcomes of grade SMP Negeri 5 Praya. From the data analysis obtained, there was not significant influence of learning motivation on students mathematics learning effect of grade SMP Negeri 5 Praya. Then for self-confidence there was found an inflence on students mathematics learning effect of grade SMP Negeri 5 Praya with the coefficient of determination of 7,3%. The results of data analysis also showed that was a significant effect between student learning motivation and self-confidence on students mathematics learning effect of grade SMP Negeri 5 Praya with the coefficient of determination of 7,4%.